Europe's rare earth element resource potential: An overview of REE metallogenetic provinces and their geodynamic setting - Goodenough, K.M.; Schilling, J.; Jonsson, E.; Kalvig, P.; Charles, N.; Tuduri, J.; Deady, E.A.; Sadeghi, M.; Schiellerup, H.; Müller, A.; Bertrand, G.; Arvanitidis, N.; et al. (Ore geology reviews, 2016)
Security of supply of a number of raw materials is of concern for the European Union; foremost among these are the rare earth elements (REE), which are used in a range of modern technologies. A number of research projects, including the EURARE and ASTER projects, have been funded in Europe to investigate various steps along the REE supply chain. This paper addresses the initial part of that supply chain, namely the potential geological resources of the REE in Europe. Although the REE are not currently mined in Europe, potential resources are known to be widespread, and many are being explored. The most important European resources are associated with alkaline igneous rocks and carbonatites, although REE deposits are also known from a range of other settings. Within Europe, a number of REE metallogenetic belts can be identified on the basis of age, tectonic setting, lithological association and known REE enrichments. This paper reviews those metallogenetic belts and sets them in their geodynamic context. The most well-known of the REE belts are of Precambrian to Palaeozoic age and occur in Greenland and the Fennoscandian Shield. Of particular importance for their REE potential are the Gardar Province of SW Greenland, the Svecofennian Belt and subsequent Mesoproterozoic rifts in Sweden, and the carbonatites of the Central Iapetus Magmatic Province. However, several zones with significant potential for REE deposits are also identified in central, southern and eastern Europe, including examples in the Bohemian Massif, the Iberian Massif, and the Carpathians. [Display omitted] •Rare earth elements (REEs) are critical for Europe's economy.•Europe has a wide range of primary REE resources.•These resources are described as metallogenetic belts in their geodynamic context.•Resources in Northern Europe are largely known in eroded alkaline igneous provinces.•Eastern and Southern Europe have many opportunities for REE exploration.